The Roles of Health Awareness and Knowledge in Medical Takaful Purchase Intention - Haji Wahab, Muhammad Zarunnaim; Mohd Tajuddin, Asma (UUM Press, 2019)
The present study aims to examine the factors of health awareness and knowledge that influence customers intention to use medical takaful coverage among the public sector officers in northern Malaysia. A quantitative research methodology was adopted to answer the objectives progressively. In the current research, data from 313 respondents were collected via questionnaires from three different organisations, namely the police department, the fire and rescue firefighter department, and the education department. Moreover, the data analysis was performed using SPSS version 22. The analysis revealed a significant and positive relationship between health awareness and knowledge and the customers intention to purchase medical takaful. Apart from that, the results also indicated that only health awareness has a significant influence on the intention with the strongest impact. On the other hand, the knowledge variable had no significant influence on customers intention to use medical takaful coverage among the respondents. A number of important limitations need to be considered in the present study which will be further explained in the conclusion section. Furthermore, the current research provides some major implications. First, on behalf of the takaful industry, the findings of the present study encourage the takaful operators, marketing teams, staffs, and agents to improve their performance by increasing their efficiency, creativity, innovation, and knowledge of product features in developing a good impression among potential customers. Second, on behalf of the public sector officers, the results of the study show the important need to enhance the customers intention to use medical takaful coverage. Third, the suitability of factors such as health awareness, knowledge and customers intention in the previous theory and literature on takaful industry has been proven in the current research. This study helps the marketing team of the takaful operators to formulate marketing strategies that can attract potential customers to participate in the medical takaful coverage, especially among the public sector officers.